The emerging role of adenosine deaminases in insects - Dolezelova, Eva; Zurovec, Michal; Dolezal, Tomas; Simek, Petr; Bryant, Peter J (Insect biochemistry and molecular biology, 2005)
Adenosine deaminases catalyze the deamination of adenosine and deoxyadenosine into their respective inosine nucleosides. Recent sequencing of the genomes of several model organisms and human reveal that Metazoa usually have more than one adenosine deaminase gene. A deficiency in the gene encoding the major enzyme is lethal in mouse and Drosophila and leads to severe combined deficiency (SCID) in human. In these organisms, enzyme deficiency causes increased adenosine/deoxyadenosine concentration in body fluids and some organs. Elevated levels of adenosine and deoxyadenosine are toxic to certain mammalian and insect cells, and it was shown for human and mouse that it is a primary cause of pathophysiological effects. Data suggest that the major role of adenosine deaminases in various taxa is the protection of tissues against increased levels of adenosine and deoxyadenosine. This review also discusses potential roles of adenosine deaminases in Drosophila metamorphosis and the employment of a Drosophila model to study the cell-specific toxicity of elevated nucleoside levels.
Keywords: Molecular Sequence Data; myši; Insecta; hmyz; sekvence aminokyselin; adenosindeaminasa; molekulární sekvence - údaje; zvířata; Humans; Mice; Amino Acid Sequence; Adenosine Deaminase; Deoxyadenosines; lidé; deoxyadenosiny; Animals